Sabotage in tournaments: Evidence from a natural experiment - Loukas Balafoutas; Florian Lindner; Matthias Sutter (Institute for the Study of Labor (IZA), 2012)
Many tournaments are plagued by sabotage among competitors. Typically, sabotage is welfare-reducing, but from an individual's perspective an attractive alternative to exerting positive effort. Yet, given its illegal and often immoral nature, sabotage is typically hidden, making it difficult to assess its extent and its victims. Therefore, we use data from Judo World Championships, where a rule change in 2009 basically constituted a natural experiment that introduced one costless opportunity for sabotage. In Judo, competitors can break an opponent's attack in an unsportsmanlike manner; these are seen as acts of sabotage. Based on a unique dataset of 1,422 fights, we find that the rule change in 2009 has led to a large increase in the use of sabotage. Moreover, sabotage is more likely to be employed by relatively less qualified individuals, and to be targeted at more qualified ones. From a survey among spectators, we show that sabotage is welfare-reducing.
urn:nbn:de:101:1-2012042310001
Keywords: C93; D03; L83; M51; M52; 330; tournaments; sabotage; Judo; natural experiment; Extensives Spiel; Feldforschung; Sport